Kewirausahaan Pembuatan Piscok Mini Lumer Dalam Kegiatan One Day Enterpreneur Di Universitas Dehasen Bengkulu - Yuliansyah Yuliansyah; Yosita Tri Purnama Sari; Ana Anjaly; Dolly Madya Parton; Muhammad Dandi Ilahi; Eko Sumartono (Pakis Journal Institute, 2024)
In this increasingly modern era, culinary trends continue to develop rapidly. One of the latest trends that is currently popular is melted mini piscok. Piscok mini melt is a variant of banana chocolate which has a smaller size and delicious filling. In 2023, melted mini piscok is predicted to become increasingly popular and become one of people's favorite foods. In 2023, melted mini piscok will experience various innovations and taste improvements that will make it even more contemporary. Various new flavors such as chocolate cheese, matcha chocolate and strawberry chocolate are a special attraction for sweet food lovers. Apart from that, the variety of shapes and appearances is also increasingly attractive with toppings such as nuts, Oreos and sprinkles which make it even more beautiful and appetizing. In facing the melted mini piscok trend in 2023, producers and sellers must be able to keep up with developments and maintain product quality they. This needs to be done to maintain consumer satisfaction and win competition with other competitors. In facing this challenge, producers must continue to carry out research and development to create new innovations that can follow consumer tastes and trends. In conclusion, piscok mini melted will become one of the popular culinary trends in 2023. Innovation and improving taste are factors main role in maintaining the popularity of this food. Apart from that, the unique and modern concept in presentation is also its own attraction. With innovation and quality improvements, it is hoped that mini melted piscok will continue to be popular and become one of the favorite foods in the years to come.